The relationship between IgA vasculitis and antioxidant activity in children - Temel, Hayrettin; Akgün, Cihangir; Okur, Mesut (Dicle University, 2021)
Objective: Immunoglobulin A vasculitis (IgAV) is the most common systemic vasculitis seen in children. The aim of this study is to investigate the relationship between malondialdehyde-induced oxidative stress, antioxidant system and organ involvement in IgAV patients. Method: 32 patients and 28 healthy children were included in the study. Serum malondialdehyde, reduced glutathione, vitamin E, vitamin C, retinol, and beta-carotene levels were measured in patients (separately in both the active and remission phases) and healthy children. Results: MDA levels were significantly higher in patients with active phase while reduced glutathione and vitamin C levels were markedly lower in both the active and the remission phases. Retinol and beta-carotene levels were lower in the active phase. It was found that retinol levels were significantly lower in patients with gastrointestinal system involvement compared to those without. Vitamin C levels were significantly lower in those with kidney involvement compared to those without. Also, a negative correlation was observed between retinol levels and the number of organs involved. Conclusion: We consider that especially vitamin C and vitamin A may be used in the treatment of IgAV. However, whether the derangements of the oxidant/antioxidant balance in the direction of increased oxidative stress are consequences or causes of the events occurring in the active phase of IgAV are open to further investigation.

Amaç: İmmünoglobulin A vaskülit (IgAV) çocuklarda en sık görülen sistemik vaskülittir. Bu çalışmanın amacı, IgAV hastalarında malondialdehit kaynaklı oksidatif stres, antioksidan sistem ve organ tutulumu arasındaki ilişkiyi araştırmaktır. Yöntemler: Çalışmaya 32 hasta ve 28 sağlıklı çocuk dahil edildi. Hastalarda (hem aktif hem de remisyon fazlarında ayrı ayrı) ve sağlıklı çocuklarda serum malondialdehit, redükte glutatyon, E vitamini, C vitamini, retinol ve beta-karoten seviyeleri ölçüldü. Bulgular: Aktif fazı olan hastalarda MDA seviyeleri önemli ölçüde daha yüksekken, redükte glutatyon ve C vitamini seviyeleri hem aktif hem de remisyon fazlarında belirgin şekilde daha düşüktü. Retinol ve beta-karoten seviyeleri aktif fazda daha düşüktü. Gastrointestinal sistem tutulumu olan hastalarda retinol düzeylerinin olmayanlara göre anlamlı derecede düşük olduğu bulundu. Böbrek tutulumu olanlarda, olmayanlara göre C vitamini seviyeleri önemli ölçüde daha düşüktü. Ayrıca, retinol seviyeleri ile ilgili tutulan organ sayısı arasında negatif bir korelasyon gözlendi. Sonuç: IgAV tedavisinde özellikle C vitamini ve A vitamininin kullanılabileceğini düşünüyoruz. Bununla birlikte, oksidan / antioksidan dengesindeki artmış oksidatif stres yönündeki düzensizliklerin, IgAV'nin aktif fazında meydana gelen olayların sonuçları mı yoksa nedenleri mi olduğu daha fazla araştırmaya açıktır.
Keywords: IgA Vasculitis; Malondialdehyde; Vitamin E; Vitamin C; Vitamin A; IgA Vasküliti; Malondialdehit; Vitamin E; Vitamin C; Vitamin A